Complications after thermal ablation for thyroid nodules across countries - Wu, Shuang; Cai, Yantao; Liu, Xiaoyu; Zhu, Chenfang (Frontiers in Endocrinology, 2025)
ObjectiveThermal ablation is an effective treatment for thyroid nodules; however, the range of complications associated with thermal ablation is unclear. In this study, we analyzed the complications of thyroid nodule thermal ablation in our hospital in combination with data from different countries for further analysis to determine the complications.Methods536 patients treated by thermal ablation at Shanghai Ninth People’s Hospital from Jan 2021 to Dec 2023 were enrolled in this retrospective study. The types and numbers of complications were recorded. Studies reporting complications of thermal ablation for thyroid nodules were identified in the PubMed database from Jan 2004 to Mar 2024. The incidence rate and types of complications were analyzed. Finally, we compared our data with those studies.ResultsTwelve types of complications associated with thermal ablation occurred to patients in our hospital. The overall incidence was 10.82%. The top five complications were pain, edema, voice changes, hematoma, and vascular reactions. In addition, 21 kinds of complications were reported across 13 countries, and the average incidence rate was 12.61%. The top five complications were pain, vocal changes, edema, hematoma, and fever. The total incidence rate did not significantly differ between our hospital and other countries (P ≥ 0.05), though the incidences of specific complications, including tracheal injury, vasovagal reaction, dyspnea, scarring, infection and fever, were significantly different (P < 0.05).ConclusionsThe incidence of complications associated with thermal ablation of thyroid nodules is similar across countries. However, the proportions and types of complications vary regionally.